2020
DOI: 10.3390/met10091219
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Beam Surface Treatment of Metals and Alloys: Techniques and Trends

Abstract: During the last decades, electron-beam treatment technologies (EBTT) have been widely used for surface modification of metals and alloys. The EBT methods are known as accurate and efficient. They have many advantages in comparison with the conventional techniques, such as very short technological process time, uniform distribution of the energy of the electron beam, which allows a precise control of the beam parameters and formed structure and properties of the materials, etc. Moreover, electron-beam treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 61 publications
(114 reference statements)
1
11
0
Order By: Relevance
“…The process involves the excitation and emission of electrons from the cathode, usually made of tungsten or a tungsten alloy. Electrons are first accelerated using very high voltage (even 300 kV) and, next deflected and directed to the working chamber using electromagnetic coils [10][11][12][13]. The design of the electron gun is presented in Figure 2.…”
Section: Electron Beam Hardeningmentioning
confidence: 99%
See 3 more Smart Citations
“…The process involves the excitation and emission of electrons from the cathode, usually made of tungsten or a tungsten alloy. Electrons are first accelerated using very high voltage (even 300 kV) and, next deflected and directed to the working chamber using electromagnetic coils [10][11][12][13]. The design of the electron gun is presented in Figure 2.…”
Section: Electron Beam Hardeningmentioning
confidence: 99%
“…The proportion of the mass subjected to electron beam hardening to the mass not subjected to hardening should be low enough for the latter to absorb heat from the surface. The above-named absorption should be fast enough to exceed the critical rate and enable the martensitic or bainitic transformation [10,12,[18][19][20].…”
Section: Electron Beam Hardeningmentioning
confidence: 99%
See 2 more Smart Citations
“…Hutsaylyuk reported that in recent decades, electron beam processing technology has been widely used for surface modification of pure metals and their alloys. This technology has significantly improved the surface properties of materials, shows new potential applications, and is promoted for industrial applications [23].…”
Section: Introductionmentioning
confidence: 99%